Experiment and analysis of a hybrid composite post-tension plate girder - Al Mustawfi, Sahib; Safiee, Nor Azizi; Abu Bakar, Nabilah; Abd Karim, Izian; Mohd Nasir, Noor Azline (Universiti Putra Malaysia, 2024)
Steel plate girders have been employed as structural bridge parts since the 19th century. They are typically made up of built-up sections in the shape of I-beams. Web and flange plates withstand shear force and bending moment, respectively. However, plate girders are vulnerable to shear buckling. Shear buckling resistance is increased by adding reinforced vertical stiffeners and, in some cases, longitudinal stiffeners. Nevertheless, these stiffeners are sometimes not enough to prevent extreme shear buckling and only delay the shear buckling of slender web panels. This study investigated a hybrid composite post-tension (HCPt) plate girder by experiment and finite element (FE) analysis. The structural performance of the HCPt plate girder was tested using three specimens: a double-web plate girder, an in-fill concrete double-web plate girder and an in-fill concrete double-web plate girder with prestress. Results showed that the steel web filled with concrete presented preferable strength and behaviour to the hollow steel web because of the concrete in-fill. It had high load capacity, strength and ductility. The concrete in-fill prevented the steel web plate from buckling, and beams generally failed in a ductile manner. Applying prestressing techniques reduced deflection under external loads, increased the load-carrying capacity and enhanced its flexural behaviour by 126% compared to the double web plate girder. The failure mode was changed from web shear buckling in a double web girder to bending in a hybrid composite plate girder, with an improvement of web shear buckling by 88%. The FE analysis result showed excellent consistency with the experimental result.